Study of menopausal symptoms, and perceptions about menopause among women at a rural community in Kerala - Sagar A. Borker; P. P. Venugopalan and Shruthi N. Bhat (Journal of Mid-life Health, 2013)
Background: Menopausal health demands priority in Indian scenario due to increase in life expectancy and growing population of menopausal women. Most are either unaware or do not pay adequate attention to these symptoms. Aims: To find the prevalence of menopausal symptoms and perceptions regarding menopause among menopausal women of Kerala. Settings and Design: A community based cross‐sectional house to house survey was conducted at Anjarakandy a field practice area under Kannur Medical College, Anjarakandy. Materials and Methods: The study was conducted among 106 postmenopausal women staying more than 6 months at Anjarakandy with the help of pretested questionnaire administered by a trained social worker from January to October 2009. Before that a pilot study was conducted and required sample size of 100 was calculated. Random sampling of houses was done. Statistical Analysis: Data was coded, entered, and analyzed using SPSS 15. Chi‐square test, proportions, and percentages were used. Results: The mean age of attaining menopause was 48.26 years. Prevalence of symptoms among ladies were emotional problems (crying spells, depression, irritability) 90.7%, headache 72.9%, lethargy 65.4%, dysuria 58.9%, forgetfulness 57%, musculoskeletal problems (joint pain, muscle pain) 53.3%, sexual problems (decreased libido, dyspareunia) 31.8%, genital problems (itching, vaginal dryness) 9.3%, and changes in voice 8.4%. Only 22.4% of women knew the correct cause of menopause. Conclusions: Thus study stated that all the ladies were suffering from one or more number of menopausal symptoms. Ladies should be made aware of these symptoms, their causes and treatment respectively.